2011
DOI: 10.1007/s00277-011-1381-2
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum anemia II: prevention and treatment

Abstract: This review focuses on the prevention and treatment of anemia in women who have just given childbirth (postpartum anemia). The problem of anemia both prepartum and postpartum is far more prevalent in developing countries than in the Western societies. The conditions for mother and child in the postpartum, nursing, and lactation period should be as favorable as possible. Many young mothers have a troublesome life due to iron deficiency and iron deficiency anemia (IDA) causing a plethora of symptoms including fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 45 publications
2
104
0
11
Order By: Relevance
“…Other publications give an overview over the changes of Hb levels during the fi rst few days after treatment with comparable results for IS [10,26,27] .…”
Section: Discussionmentioning
confidence: 83%
“…Other publications give an overview over the changes of Hb levels during the fi rst few days after treatment with comparable results for IS [10,26,27] .…”
Section: Discussionmentioning
confidence: 83%
“…14,15 O ferro é um elemento importante para o desenvolvimento do cérebro fetal e de habilidades cognitivas do recém-nascido. 16 O crescimento do cérebro demanda uma suplementação de ferro balanceada através da barreira hematoencefálica. 17 No feto e no recém-nascido, a deficiência de ferro pode causar dano permanente ao cérebro e afetar de forma negativa a inteligência, as habilidades cognitivas e o comportamento durante a infância e a idade adulta.…”
Section: Complicações Na Gravidezunclassified
“…Por outro lado, na maioria dos países em desenvolvimento, é indicada a profilaxia universal de ferro, e altas doses de ferro por via oral podem ser recomendadas de acordo com o status de ferro em populações específicas de mulheres em idade fértil e gestantes. 16 Não existe um consenso nos países ocidentais acerca do uso profilático de ferro na gestação. Alguns países como a Dinamarca preconizam a administração de ferro profilático enquanto outros como a Noruega não recomendam tal prática.…”
Section: Profilaxia E Tratamentounclassified
“…A review has identified that anaemia in both antenatal and postpartum women is more prevalent in developing countries than in Western societies (106).…”
Section: Iron (Fe)mentioning
confidence: 99%
“…The prophylaxis of postpartum anaemia should begin in early pregnancy with prophylactic oral ferrous iron supplements 30-50 mg daily (106). In the treatment of slight-to-moderate postpartum iron deficiency anaemia, the first choice is oral ferrous sulfate 100 to 200 mg daily.…”
Section: Iron (Fe)mentioning
confidence: 99%